The Influence of Mo Additions on the Microstructure and Mechanical Properties of AlCrFe2Ni2 Medium Entropy Alloys - Gein, Sergej; Witusiewicz, Victor T.; Hecht, Ulrike (Frontiers in Materials, 2020)
The alloy system Al-Cr-Fe-Ni provides means for developing novel duplex materials composed of face-centered cubic (FCC) and body-centered cubic (BCC) phases with nearly equal volume fraction. We performed an alloy development study starting from the medium entropy alloy AlCrFe2Ni2 and adding small amounts of molybdenum in the following series (at.%): Al17Cr17Fe33Ni33, Al17Cr17Fe33Ni33Mo1, Al16Cr16Fe33Ni33Mo2, Al16Cr16Fe33Ni33Mo3. We focused the research on samples with an ultrafine vermicular duplex microstructure, a unique structure requiring sufficiently high cooling rates to suppress the conventional Widmanstätten colony formation. The samples were produced by arc melting in buttons of 300 g each. We characterized the microstructure of the samples using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS) and electron backscatter diffraction (EBSD). The EBSD results revealed significant strain in the FCC phase, which is characteristic for the ultrafine vermicular duplex microstructure and its specific formation pathway. We investigated mechanical properties of the samples by micro-indentation and 3-point bending in a miniature testing device. The test specimens were in the as-cast condition, as well as in distinct annealed conditions. Annealing treatments were carried out at 950 °C and 1100 °C under argon. The annealing lasted from 10 minutes to 6 hours, followed by water quenching. Prolonged annealing at 950 °C of Mo-containing samples resulted in the formation of sigma-phase. Annealing at 1100 °C safely avoided sigma-phase formation, while leading to a good balance between the flexural strength and ductility of these samples. Mechanical testing also included the well-established superduplex steel 1.4517 (DIN EN 10283 / ASTM A890) as reference material.